2014
DOI: 10.1186/1472-6920-14-89
|View full text |Cite
|
Sign up to set email alerts
|

Cheating on examinations and its predictors among undergraduate students at Hawassa University College of Medicine and Health Science, Hawassa, Ethiopia

Abstract: BackgroundCheating on examinations in academic institutions is a worldwide issue. When cheating occurs in medical schools, it has serious consequences for human life, social values, and the economy. This study was conducted to determine the prevalence of cheating and identify factors that influence cheating among students of Hawassa University College of medicine and health science.MethodsA cross sectional study was conducted from May through June 2013. A pre-tested self-administered, structured questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 24 publications
6
31
1
1
Order By: Relevance
“…Approximately half of the present study participants stated that they cheated in exams while being a student, which is consistent with the results of a study reporting the phenomenon of cheating as a dilemma in education (2). In the last five years, 117 articles have been published on cheating according to the PubMed data bank.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Approximately half of the present study participants stated that they cheated in exams while being a student, which is consistent with the results of a study reporting the phenomenon of cheating as a dilemma in education (2). In the last five years, 117 articles have been published on cheating according to the PubMed data bank.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, less than half of students admitted that their cheating had been discovered by the examiners and sometimes had led to their expulsion from the exam session.Desalegn and Behranreported that the cheating of the majority of participants (80.1%) was not disclosed and that students do not report cheating to exam proctors even if they witness cheating (2). Increased levels of supervision by exam proctors during exam sessions may affect the identification of those cheating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmadi's (2012) study of 132 language students in a university in Iran, revealed that cheating is prevalent 'justified' by various reasons such as "not being ready for exams"; "the difficulty of the exams"; "lack of time to study" and "careless and lenient instructors." A recent study by Desalegn and Berhan (2014) reported that undergraduate medical students in Hawassa, Ethiopia cheated mainly on the entrance examinations and students who cheated in high school had a higher tendency to cheat when entering the university. This finding can be extrapolated to tie in with that of the study mentioned earlier on the report of the cheating among high schools students in the US.…”
Section: Introductionmentioning
confidence: 99%
“…For years, AD has been considerably studied and debated (Huang, Yang & Chen, 2015;Desalegn & Berhan, 2014) ) as a topic of concern among university educators. AD, according to Callahan (2004) can be defined as a type of rule-breaking behaviour undertaken by an individual to get ahead of others academically, professionally or financially.…”
Section: Introductionmentioning
confidence: 99%